The Policy of Visa-Free Visit Arrangements in Indonesia for International Visitor - Nur Fatehi; Ade Riusma Ariyana; Devina Arifani (Jurnal Daulat Hukum, 2023)
This article is entitled "Setting Visa-Free Policy in the Order of Increasing Visits of International Tourists to Indonesia", which aims to examine the arrangements for visiting visa-free policies in order to increase foreign tourist visits to Indonesia and find out the sanctions that can be imposed on recipients of visa-free visits who violate and misuse of a visit stay permit. In order to improve relations between the Republic of Indonesia and other countries, it is necessary to provide convenience for foreign nationals to enter the territory of the Republic of Indonesia which is carried out in the form of exemption from the obligation to have a visit visa with due observance of the principle of reciprocity and the principle of benefit. The Government of Indonesia issued Presidential Regulation Number 21 of 2016 concerning Free Visit Visas. This regulation was made in order to provide benefits to improve the economy in general and increase the number of foreign tourist visits in particular. The research method used in this study is a normative legal research method through a statutory approach. The discussion is directed at the implications of applying the visa-free policy from an employment perspective and how the government will handle it. The visit visa-free policy is regulated in Presidential Regulation Number 21 of 2016 concerning Visit Visa-free and Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 17 of 2016.